Production of texts in students from two public universities with intercultural model - Bastiani-Gómez, José (2015)
The objective of this study was to identify and analyze the characteristics of the written communication of the Language and Culture students at Chiapas Intercultural University and the Early Education and Elementary School Education students at the National Pedagogical University, Unit 071, in Tuxtla Gutierrez, Chiapas and its relation with their intercultural training.  The nature of the study is exploratory and descriptive and used a survey, participant observation and a group interview with a convenience sample of eighty-three students which allowed the reflection on and the discussion about the characteristics of the students’ written production based on the analysis of their written production and their reading-writing experiences. Results indicate that the most serious problems are topic development and coherence.  Students claim that they have received poor schooling which has ignored their ethnical background.  These difficulties are due to lacks in their teaching training, the precarious condition of school organization, the lack of reflection on bilingual education, the advisor’s lack of ethical commitment and the deficient training received by their professors and advisors.  The article argues that teacher education must be intercultural, including teaching strategies appropriate for both the indigenous language and Spanish.